Perbedaan Ukuran Gigi Laki-laki dan Perempuan Suku Jawa dengan Maloklusi Kelas I Angle Berdasarkan Analisis Bolton - Eko Prastyo; Basma R. Prakosa; Raden Aditya W. Wardana; Muhammad R. Arnol (e-GiGi, 2023)
Abstract: Factors that cause differences in tooth size are inter alia gender, race, and the presence of dental anomalies whether in the forms of abnormalities in location, size, shape, or number of teeth which can cause dental malocclusion. This study aimed to determine whether there was a difference in tooth size of Javanese men and women who had Angle Class I malocclusion based on Bolton's analysis. This was an analytical and observational study. Samples consisted of 54 dental models with Angle Class I malocclusion of the Javanese ethnic group divided into two groups, namely 27 male dental models and 27 female dental models. The mesiodistal width of each tooth was calculated except for the second and third molars. The calculation of the anterior ratio and the overall ratio was based on the Bolton analysis formula. Each sample was calculated for the upper and lower jaws, and then the results of the calculations were processed and analyzed using the independent t-test. The anterior ratio of the female had a value of 79.8081±3.45013, the anterior ratio of the males had a value of 78.7763± 3.55517, the overall ratio of the females had a value of 92.5041±1.97414, and the overall ratio of the male had a value of 92.2807±2.61955. In conclusion, by Bolton analysis, there was no significant difference in tooth sizes between Javanese men and women who had Angle Class I malocclusion. Keywords: tooth size; Bolton analysis; Angle Class I malocclusion; Javanese   Abstrak: Perbedaan ukuran gigi disebabkan antara lain oleh jenis kelamin, ras, dan adanya anomali gigi berupa kelainan letak, ukuran, bentuk, dan jumlah gigi yang dapat mengakibatkan terjadinya maloklusi gigi. Penelitian ini bertujuan untuk mengetahui apakah terdapat perbedaan ukuran gigi laki-laki dan perempuan suku Jawa yang mengalami maloklusi kelas I Angle berdasarkan analisis Bolton dengan menggunakan metode observasional analitik. Sampel berjumlah 54 model gigi dengan maloklusi kelas I Angle yang berasal dari suku Jawa, dibagi menjadi dua kelompok yaitu 27 model gigi laki-laki dan 27 model gigi perempuan. Model gigi yang didapat dilakukan perhitungan lebar mesiodistal setiap gigi kecuali gigi molar kedua dan molar ketiga. Perhitungan rasio anterior dan rasio keseluruhan berdasarkan rumus analisis Bolton. Setiap sampel dilakukan perhitungan rahang atas dan rahang bawah, kemudian hasil perhitungan diolah dan dianalisis menggunakan uji t-test independent. Rasio anterior perempuan memiliki nilai 79,8081±3,45013, rasio anterior laki-laki memiliki nilai 78,7763±3,55517, rasio keseluruhan perempuan memiliki nilai 92,5041±1,97414, dan rasio keselu-ruhan laki-laki memiliki nilai 92,2807±2,61955. Simpulan penelitian ini ialah dengan analisis Bolton, tidak terdapat perbedaan bermakna ukuran gigi antara laki-laki dan perempuan suku Jawa yang memiliki maloklusi Kelas I Angle. Kata kunci: ukuran gigi; analisis Bolton; maloklusi kelas I Angle; suku Jawa